THE INFLUENCE OF THE WELLNESS TOURISM NATURE ART, EART AND EMOTION PROGRAM ON THE MENTALITY OF GENERATION Z - Dadan Ramdani (RADJA PUBLIKA, 2025)
The background of this study is the increasing psychological pressure, stress, and anxiety among Generation Z due to intense social media exposure, academic and career competition, and rapidly changing social dynamics. The Wellness Tourism program that integrates elements of nature, art, connection with the earth, and emotional management is believed to be an alternative holistic approach to improving the mental resilience and psychological well-being of this generation. The purpose of this study is to determine the extent to which the program is effective in influencing aspects of the mentality of Generation Z, which include self-confidence, emotional stability, self-awareness, and a positive life orientation. This study uses qualitative methods. The results show that this activity invited several generation Z communities in Bandung to take part in wellness tourism art, ear and emotion activities. The concept of wellness tourism at this time is very useful for the sustainability of public health, especially generations. The community service program that focuses on the Z generation aims to increase awareness of the environment related to the state of the natural environment that needs to be preserved, then maintain and relax mental health for the generation from their busy schedule to enjoy the beauty and pleasant natural atmosphere. This program is divided into three stages, namely preparation, implementation, monitoring and evaluation. This wellness tourism program can be implemented well because generation z has better post-test scores than the pretest.